STUDENTS' PERCEPTION OF THE USE OF DIGITAL STORYTELLING IN TEACHING READING NARRATIVE TEXT - sartika, deti; syafryadin (Indonesian Journal of Educational Development (IJED), 2025)
This study investigates students' perceptions of digital storytelling as a pedagogical tool for teaching reading narrative texts, particularly in the context of English as a Foreign Language (EFL) education. With the increasing integration of technology in educational settings, digital storytelling has emerged as an innovative method that combines traditional storytelling with multimedia elements, thereby enhancing student engagement and comprehension. Conducted at SMAN 5 Lubuk Linggau, the research utilized a survey design to gather insights from EFL students regarding their experiences and attitudes towards digital storytelling. The findings reveal a predominantly positive perception among students, who believe that this method not only makes reading more enjoyable but also fosters a deeper understanding of narrative content. However, the study also uncovers concerns about the potential for disinterest among some students, highlighting the need for thoughtful implementation by educators. By tailoring digital storytelling experiences to align with students' interests and learning needs, educators can maximize its effectiveness and enrich the reading experience. The study contributes valuable insights into the role of digital storytelling in education, advocating for its continued exploration and integration to enhance student learning outcomes and engagement in reading narrative texts.